The Housing Occupancy Ratio in the Palestinian Territories - Ahmad, Hussein; Tayeh, Hanan (Jordan Journal of Social Sciences, 2020)
This study aimed to analyze the housing occupancy ratio in the Palestinian Territories, and the factors affecting it, through the data provided by the survey of housing conditions in 2015, which was conducted by the Palestinian Central Bureau of Statistics. To achieve the goals of the research, the descriptive and analytical approaches were used. The housing occupancy ratio in the Palestinian Territories has reached 1.84 persons per room, and this degree varied between 1.71 persons per room in the West Bank to 2.08 persons per room in the Gaza Strip. The variables of the type of housing, the housing space, the governorate, the type of locality, the work of the head of the household, the educational level of the head of the household had a clear effect of variations on the degree of occupancy ratio.